Implementation of TOPSIS Algorithm for Selection of Prominent Student Class. Issue 1 (February 2021) - Siregar, Victor Marudut Mulia; Sonang, Sahat; Purba, Arifin Tua; Sugara, Heru; Siagian, Nancy Florida
Abstract: This study aims to provide the right solution in overcoming the problem of selection for prominent class students senior high school at SMAN 2 Pematangsiantar. The solution is to make a decision support system for the selection of prominent class XI IPA students in determining rankings. The method used is the TOPSIS (Technique for Order Performance by Similarity to Ideal Solution) algorithm by using several criteria, namely: Mid Test Score, Final Exam Score, Extracurricular, Personality, and Attitude. The results of student data processing using the decision support system obtained weights of 1, 0.57188272655161, and 0.56259472567445 for rank 1 to rank 3. The implementation of this Decision Support System is beneficial and makes it easier for the school and the homeroom teacher to determine ranking for the selection of prominent class students.